Designing Model and Strategy for Strenghthening The Competitiveness of Small Medium Enterprises - D. Darwanto; Purbayu Budi Santosa; Nenik Woyanti; B. Bambang (ETIKONOMI, 2018)
Strengthening the competitiveness of SMEs in Indonesia was essential by the era of global competition in line with the implementation of the ASEAN economic community in 2015. The purpose of this research is designing a model and strategy of strengthening the international competitiveness of SMEs through LEDI - 9F approach. This research is using content analysis and Analytic Networking Process. This research found that the model of strengthening the international competitiveness of SMEs could be done through a model of partnership between the various stakeholders both at district, provincial and state levels. The most priority aspect to strengthen SME's competitiveness is business context with the most priority strategy that is the strategy of management and business. Based on the results of the analysis, the government can use as a reference for the government to strengthen SME's competitiveness through anticipate problems and optimize the solutions that arise in enhancing SME's competitiveness.DOI: 10.15408/etk.v17i1.6826